A comparative study of gray matter volumetric alterations in adults with attention deficit hyperactivity disorder and bipolar disorder type I. (November 2022) - Xie, Hongsheng; Cao, Yuan; Long, Xipeng; Xiao, Hongqi; Wang, Xiuli; Qiu, Changjian; Jia, Zhiyun
Abstract: Background: Attention deficit hyperactivity disorder (ADHD) and bipolar disorder type I (BD-Ι) share great overlapping symptoms and are highly comorbid. We aimed to compare and obtain the common and distinct gray matter volume (GMV) patterns in adult patients. Method: We searched four databases to include whole-brain voxel-based morphometry studies and compared the GMV patterns between ADHD and healthy controls (HCs), between BD-I and HCs, and between ADHD and BD-I using anisotropic effect-size signed differential mapping software. Results: We included 677 ADHD and 452 BD-Ι patients. Compared with HCs, ADHD patients showed smaller GMV in the anterior cingulate cortex (ACC) and supramarginal gyrus but a larger caudate nucleus. Compared with HCs, BD-Ι patients showed smaller GMV in the orbitofrontal cortex, parahippocampal gyrus, and amygdala. No common GMV alterations were found, whereas ADHD showed the smaller ACC and larger amygdala relative to BD-Ι. Subgroup analyses revealed the larger insula in manic patients, which was positively associated with the Young Mania Rating Scale. The decreased median cingulate cortex (MCC) was positively associated with the ages in ADHD, whereas the MCC was negatively associated with the ages in BD-Ι. Limitations: All included data were cross-sectional; Potential effects of medication and disease course were not analyzed due to the limited data. Conclusions: ADHD showed altered GMV in the frontal-striatal frontal-parietal circuits, and BD-Ι showed altered GMV in the prefrontal-amygdala circuit. These findings could contribute to a better understanding of the neuropathology of the two disorders. Highlights: ADHD and BD-Ⅰ showed different altered GMV patterns and pathophysiology. Impulsivity and mania might be conducted by different neural substrates. Direct comparisons are vital to furyther study common and distinct brain changes.